THE EFFECT OF SCHOOL PRINCIPALS’ SITUATIONAL LEADERSHIP, PROFESSIONAL COMPETENCE, AND WORK COMMUNICATION ON THE WORK MOTIVATION OF TEACHERS AT PUBLIC HIGH SCHOOLS IN BALANGAN REGENCY - Raihani Raihani; Aslamiah Aslamiah; Ahmad Suriansyah (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the influence of school principals’ situational leadership, teachers’ professional competence, and workplace communication on the job motivation of public high school teachers in Balangan Regency, both directly and indirectly through workplace communication as a mediating variable. The study employed a quantitative approach with an explanatory research design. The study population consisted of all public high school teachers in Balangan Regency who held certified educator status, totaling 108 individuals, who were also used as the study sample. Data collection was conducted using a questionnaire that had passed validity and reliability tests. Data analysis was performed using descriptive statistics, classical assumption tests, multiple linear regression analysis, and path analysis with the assistance of SPSS software. The results of the study indicate that the principal’s situational leadership has a positive and significant effect on teachers’ work motivation (β = 0.155; p < 0.05), teachers’ professional competence has a positive and significant effect on teachers’ work motivation (β = 0.378; p < 0.001), and work communication has a positive and significant effect on teachers’ work motivation (β = 0.142; p < 0.05). Furthermore, the principal’s situational leadership has a significant effect on work communication (β = 0.505; p < 0.05), and teachers’ professional competence also has a significant effect on work communication (β = 0.623; p < 0.05). The path analysis results indicate that workplace communication mediates the effects of the principal’s situational leadership and teachers’ professional competence on teachers’ work motivation. These findings confirm that improving the quality of adaptive leadership, strengthening professional competence, and developing effective workplace communication are complementary strategies for enhancing teachers’ work motivation and supporting improvements in the quality of education at public high schools in Balangan Regency.